O olhar sobre a capoeira : um estudo dos filmes nacionais e internacionais - Silva, Daniel Junior da (2013)
This study focuses on representations of capoeira move made by Brazilian and foreign film productions and its development process related to the idea of Brazilian culture. Having a source analysis feature films produced in Brazil and abroad, where capoeira appears directly or indirectly, seek to identify the images elements and mechanisms used to present the roost and the relationship of these elements appropriations between national productions and international. Understanding the characteristics that make up the visuals, audio and textual evidence to present themselves as a visible or not visible in films, and may reveal the processes of appropriation and struggles of representations on the understanding of poultry to be designed to viewers, conducted within this methodological process, perusal, detective, connecting points and interrogating them with other sources. The research points to date, that the decade 1950-2012 capoeira undergoes transformations and resignifications film, where it is used in the process of affirmation of the culture and identity of the Brazilian people, is the idea of sportivization or the redemption of demonstrations the origin of Brazil. Thus, capoeira is marked by discontinuities in the development process as a cultural practice, assuming various shapes and moving away from the traditional discourse, in which there is a continuity guided by molds originality, expressed at the time of capture of moving images and made circular in Brazilian and abroad imagination.